Frontispiece: Chameleonic Behavior of the α‐Methylcyclopropyl Group and Its Through‐Space Interactions: A Route to Stabilized Three Redox States in Diarylnitroxides. Issue 30 (27th May 2020) - Levitskiy, Oleg A.; Dulov, Dmitry A.; Bogdanov, Alexey V.; Grishin, Yury K.; Nefedov, Sergey E.; Magdesieva, Tatiana V.
Abstract : The most stable nitroxides of the diaryl‐type known to date ( τ 1/2 in benzene exceeds three months, as it is illustrated in the cover art) are presented. As an efficient structural "instrument" for stabilization of both open‐shell and ionic states of diaryl nitroxides, the α‐methylcyclopropyl group with conformationally dependent electronic properties is suggested. Conformational switching of the cyclopropyl orientation relatively to the adjacent aromatic π system as dependent on the nitroxide's redox state, are confirmed by DFT calculations and experimental results. More information can be found in the Full Paper by T. V. Magdesieva et al. on page 6793 ff.